War Crimes Within The Framework of International Humanitarian Law And The Rome Statute: An Analytical Study of Israel-Palestine Conflict - Iskandar Iskandar; Irsan, Muhammad Irsan; Didin Nurul Rosidin; Uu Nurul Huda; Ryan Fachryan Lesmana Putra (Jurnal Ius Constituendum, 2026)
This study aims to examine how war crimes are conceptualised and enforced within the framework of International Humanitarian Law (IHL) and the Rome Statute by analysing the Israel–Palestine conflict as a prolonged and politically contested armed conflict in which serious violations against civilians persist with limited accountability. Using a normative legal research design, this article applies a statutory and case-based approach through doctrinal analysis of the Geneva Conventions, Additional Protocols, and the Rome Statute, supported by qualitative examination of ICC-related documents, United Nations reports, and verified secondary data to assess the implementation of core IHL principles, particularly distinction and proportionality. The findings demonstrate that recurrent violations committed by both parties are not primarily caused by normative gaps in international law, but rather by structural enforcement barriers, including the ICC’s jurisdictional and admissibility constraints, restricted access to evidence, lack of state cooperation, political interference, and selective enforcement through international institutions, especially the UN Security Council. These obstacles contribute to an enduring enforcement deficit that weakens civilian protection and perpetuates impunity in asymmetric and protracted conflicts. The novelty of this study lies in systematically linking fundamental IHL principles—distinction, proportionality, and the prohibition of excessive force—to their qualification as war crimes under Article 8 of the Rome Statute, while critically demonstrating how political realities and institutional dependence on state cooperation undermine the effectiveness of international criminal accountability mechanisms. This research highlights the urgent need to strengthen coordination among international institutions, enhance investigative access and evidentiary reliability, and promote more consistent and impartial enforcement strategies to ensure that IHL and international criminal law operate as effective deterrents and justice-delivering instruments in contemporary armed conflicts.